Effects of genetic polymorphism in Pit1, GH, GHR and KCN3 on milk yield and body weight of Khuzestan (Iran) water buffaloes - Meysam Ahmadzadeh (Universidad de Antioquia, 2019)
Background: Genetic information is necessary to devise strategic plans aimed to improve the genetic merit of buffalos. Objective: To assess the effect of genetic polymorphisms in GH, Pit-1, GHR, GHRHR, and KCN3 genes on milk production and body weight of Khuzestan water buffaloes. Methods: Blood samples were collected from 60 buffaloes from the Khuzestan province, Iran. Using the PCR-RFLP technique, the amplified and digested fragments of GH/AluI, GHR/AluI, GHRHR/ HaeIII, Pit1/HinfI, and KCN3/HindIII were genotyped. Results: All animals were monomorphic for GHRHR. The frequency of mutant alleles for GH, GHR, KCN3, and Pit1 was 47.5, 74.2, 49.2, and 51.7%, respectively. There were significant differences (p<0.0001) in the genotypic frequencies of GH, GHR, and Pit1 between high and low milk-yielding buffaloes. The GH (p=0.0002), GHR (p<0.0001) and Pit1 (p<0.0001) polymorphisms also had significant effects on body weight. Sequencing results revealed the presence of C496A, G495A, G498A and C1501T SNPs in the GH, and G1702T in the GHR gene of Khuzestan buffalos. Conclusion: This study highlights the importance of GH, GHR, and Pit1 on milk production and body weight of Khuzestan buffaloes. The results suggest that devising an integrated breeding plan in Khuzestan water buffalos can considerably benefit from the very high diversity in candidate genes.